DETERMINATION OF GRAVITY ACCELERATION USING PHYSICAL PENDULUM EXPERIMENT AND PARABOLIC MOTION - R. (NIM:20207082), HERNELIS
Experiment to determine gravitational accceleration has been done using physical pendulum and parabolic motion principles. Two pendulum masses were used namely 0.4 kg and 0.6 kg. Gravitational acceleration for each mass is g = 9.295 m/s2 and g = 9.126 m/s2. These results are close enough to the literature 9.81 m/ s2 . Relative error of this gravity determination for each pendulum are 5.3 % and 6.9 %.